ANALISIS ISI PESAN DAKWAH PADA RUBRIK DIALOG JUM’AT KORAN LOMBOK POST - Fitriani, Rina (KOMUNIKE: Jurnal Komunikasi Penyiaran Islam, 2018)
The Friday dialogue rubric is published so that there is abalance between general studies and religion, not only providing general information but also descriptive information about the Islamic religion. And it must be acknowledged that knowledge about religion, especially those relating to daily life, is needed by the community, especially the Muslim community in NTB. With the existence of print media, it will be easier to access and obtain information about a matter contained in the missionary message. The role of da’wah in the print media prioritizes the interests of the reader, strives to increase intelligence and welfare through information. Newspapers as Media Da’wah are the media and mouthpieces of the nation’s progress. This paper will focus on the discussion of the analysis of the contents of the da’wah message at the Lombok Post Newspaper in the Friday Dialogue Edition of the August 2017 Edition.